Trust and information communication technology as the determinants of virtual team performance: a study among millennials - Hashim, Nurhazirah; Mohd Yusof, Ahmad Nizam; Ahmad, Nor Lela; Abdul Rahman, Ramlee; Juhdi, Nurita (2014)
The turbulent and complexity of technological advances of systems that keep changing rapidly contribute to most of the result in measuring company performance. High performance virtual teams are competent in a broad array of scientific disciplines as the communication technologies become a vital in supporting the virtual organization. Nonetheless, virtual teams face particular challenges to build successful interactions and effective communication that is even more critical for success in the virtual setting. Meanwhile, the growth of Millennial generation constitute to the upcoming of virtual teams as the population keep growing with the pace of technologies. Besides, Millennials are illustrated as generation cohort that have an admirable attributes from organizations’ perspectives due to they are more accepting of diversity, have capabilities to cope with advanced communication and information technologies, have the ability to see the holistic view of a problem and more comfortable working with teams rather than past generations. Therefore, the objective of this study is to investigate the relationships among determinants of virtual team namely; trust and information communication technology and virtual team performance for Millennials. Hence, the proposed conceptual framework for the pertaining issues is hoped to be indicator for future researcher to expand more on the determinants of virtual team performance among especially in Malaysia setting.